WHAT FACTORS INFLUENCE THE DEVELOPMENT OF READING FLUENCY OF ROMA CHILDREN? THE EFFECTS OF WHOLE-CLASS REPEATED READINGS AND SCHOOL ABSENTEEISM - DACIAN DORIN DOLEAN; IOANA ȚINCAȘ; CRINA DAMȘA (Studia Universitatis Babes-Bolyai, 2016)
ABSTRACT. Research literature shows that Roma children's literacy skills are less developed compared with their non‐Roma peers. This situation represents a major deterrent in integration of Roma within the majority of countries of European Union. In this study we measured the effects of an intervention program aimed to diminish the gap in reading fluency skills between Roma and non‐Roma 2nd grade children. The results indicated that a) Roma children's performance was significantly lower than their non‐Roma peers before and after the intervention, b) there was no difference in the reading fluency growth rate of Roma and non‐Roma children and c) poor school attendance of Roma children moderated the effect of Roma ethnicity. The findings suggest that poor school attendance has a particularly significant negative effect on the development of reading fluency of children of Roma ethnicity.